Doxorubicin/Nucleophosmin Binding Protein-Conjugated Nanoparticle Enhances Anti-leukemia Activity in Acute Lymphoblastic Leukemia Cells in vitro and in vivo - Gan, Donghui; Chen, Yuwen; Wu, Zhengjun; Luo, Liping; Yirga, Shimuye Kalayu; Zhang, Na; Ye, Fu; Chen, Haijun; Hu, Jianda; Chen, Yingyu (Frontiers in Pharmacology, 2021)
Acute lymphoblastic leukemia (ALL) is an aggressive malignancy. Adults with ALL have more than 50% relapse rates. We have previously validated that overexpression of nucleophosmin (NPM) is involved in the multidrug resistance (MDR) development during ALL; and a synthetically engineered recombinant NPM binding protein (NPMBP) has been developed in our group; NPMBP and doxorubicin (DOX) can be conjugated in a nanoparticle-based drug delivery system named DOX-PMs-NPMBP to counteract MDR during ALL. Here, we evaluated the antileukemia potential of DOX-PMs-NPMBP in resistant ALL cells. This study demonstrates that DOX-PMs-NPMBP significantly enhances chemosensitivity to DOX in ALL cells. Despite at variable concentrations, both resistant and primary ALL cells from relapsed patients were sensitive to DOX-PMs-NPMBP. In detail, the half maximal inhibitory concentration (IC50) values of DOX-PMs-NPMBP were between 1.6‐ and 7.0‐fold lower than those of DOX in cell lines and primary ALL cells, respectively; and apoptotic cells ratio was over 2‐fold higher in DOX-PMs-NPMBP than DOX. Mechanistically, p53-driven apoptosis induction and cell cycle arrest played essential role in DOX-PMs-NPMBP-induced anti-leukemia effects. Moreover, DOX-PMs-NPMBP significantly inhibited tumor growth and prolonged mouse survival of ALL xenograft models; and no systemic toxicity occurrence was observed after treatment during follow-up. In conclusion, these data indicate that DOX-PMs-NPMBP may significantly exert growth inhibition and apoptosis induction, and markedly improve DOX antileukemia activity in resistant ALL cells. This novel drug delivery system may be valuable to develop as a new therapeutic strategy against multidrug resistant ALL.